Implementation of Islamic Values in Learning in Islamic College - Arlina, Arlina; Daulay, Haidar Putra; Azhar, Ihsan Satrya (AT-TA'LIM, 2025)
This study aims to describe the application of Islamic values in the learning process at three Islamic universities in Medan City, namely UISU, UMSU, and UINSU. The informants in this study numbered 18 people, namely 2-3 lecturers in each faculty, who were selected purposively based on their relevance in the application of Islamic values in the general learning process. The approach used is descriptive qualitative, with data collection techniques through interviews, observations, and documentation of lecturers and students from various faculties. The results of the study indicate that the Islamic values applied in learning include 19 main values such as discipline, responsibility, mutual respect, and tolerance. The process of internalizing these values takes place in stages starting from the stage of knowing, feeling, to acting. Each university has a different pattern of implementation, ranging from non-formal approaches to integration into the official curriculum. Although effectiveness varies between institutions, overall implementation shows a positive direction towards learning based on Islamic values that are integrated with mastery of knowledge